Penyusunan Peta Koefisien Amplifikasi Berdasarkan Rasio Spektra Percepatan - Elvis Saputra (Rekayasa Sipil, 2023)
One of the most important parameters in the building structure design process is an amplification coefficient. The amplification coefficient is needed to propagate a spectra acceleration at bedrock to soil surface. The amplification coefficient can be determined by several methods such as MASW Method, HVSR Method and other methods. One alternative method that can be used in determining the amplification coefficient is to determine the ratio between the ground acceleration at the surface and at the bedrock. Therefore, the purpose of this study was to identify the amplification coefficient in the Province of the Special Region of Yogyakarta with the PSHA method analysis approach by utilizing the shear wave velocity data (Vs30). This research method was carried out in 3 stages, namely data collection, acceleration analysis using the PSHA method, and determination of the amplification coefficient based on the acceleration ratio. The results of the study obtained a distribution of the amplification coefficient of the acceleration spectra of 0.2 and 1 second in the DIY province with a maximum value of Fa amplification coefficient was 1.414 on hard soil conditions and 1.653 on medium soil conditions. The maximum Fv amplification coefficient was 1.508 on hard soil conditions and 1,923 on medium soil conditions.